The application of theory in international investment - Jankanakittikul, Thanomsilp; Namnai, Asst. Prof. Dr. Kriengkrai (Journal for Developing the Social and Community, 2018)
International investment is a part of driving the global economy. At present, many businesses and entrepreneurs are investing in doing business abroad. There are many factors that make the decision to invest in that country. The study of foreign investment theory. It should also learn about foreign investment theory as it affects economic policy. Investments in both government and private sectors. The result of this study is the concept of international investment theory. Learn about education. Foreign Investment research case study of foreign invested companies. Then applied to the theory of international investment.